ANALISIS KEBUTUHAN AIR BERSIH DI KOTA PAGAR ALAM - Lily Endah Diansari (Jurnal Ilmiah BERING, 2022)
Clean water is needed to meet daily needs, all Indonesia people have the right to get decent and affordable clean water infrastructure and facilities. In Pagar Alam city still many residents who have not been served supply of clean water, where this needs to be anticipated considering the need for clean water for the community from year to year continues to grow. This relead to determine the needs of clean water needed by the people of Pagar Alam city. In this research method estimate clean water needs besed on geometric, dan arithmetic methods and based on existing dat plans. Calculation came back that there was a need for clean water in cities Pagar Alam by the year 2023 it was estimated to be 374,277 liters/second, the need for reservoirs in cities Pagar Alam by the year 2023 it was estimated to be 6.061,001